Dihydropyrimidinase deficiency: phenotype, genotype and structural consequences in 17 patients - Kuilenburg, André van; Dobritzsch, Doreen; Meijer, Judith; Meinsma, Rutger; Benoist, Jean-François; Assmann, Birgit; Schubert-Bast, Susanne; Hoffmann, Georg F.; Duran, Marinus; de Vries, Maaike C.; Kurlemann, Gerd; Eyskens, François J. M.; et al. (Biochimica et biophysica acta. Molecular basis of disease, 2010)
Dihydropyrimidinase (DHP) is the second enzyme of the pyrimidine degradation pathway and catalyses the ring opening of 5,6-dihydrouracil and 5,6-dihydrothymine. To date, only 11 individuals have been reported suffering from a complete DHP deficiency. Here, we report on the clinical, biochemical and molecular findings of 17 newly identified DHP deficient patients as well as the analysis of the mutations in a three-dimensional framework.
Gesehen am 29.08.2023